MOOD TYPE AND APPRAISAL REALIZED IN THE ONLINE JAKARTA POST EDITORIAL ISSUED ON MARCH 12TH, 2018 "VOTERS NEED MORE CANDIDATES" - Alpian Bagus Pratama; Katharina Rustipa (Dinamika Bahasa dan Budaya, 2020)
This research attempt to investigate an editorial text of the online Jakarta Post entitled “Voters Need More Candidates” Issued on March 12th, 2018 with two research questions, i.e. (1) What kinds of mood system are realized in the text of “Voters need more candidates”? (2) What kinds of author’s attitude, engagement and graduation are reflected in the text? This research used qualitative research tradition Method. This research found out that the type of mood mostly used in editorial text entitled Voter Need More Candidates is declarative. The lexical of appraisal system are Judgment-Attitude (9%) and Appreciation Attitude (91); Mono-glossic-Engagement (36.84%), Dialogic Contraction-Engagement (15.79%) and Dialogic Expansion-Engagement (47.37%)); Force-Graduation (100%).